A COMPARATIVE STUDY OF CORRELATION BETWEEN CENTRAL CORNEAL THICKNESS AND INTRAOCULAR PRESSURE IN PRIMARY OPEN-ANGLE GLAUCOMA WITH HEALTHY CONTROL SUBJECTS - Chouhan, Anil; Meena, Sajjan Singh; Lakshita Maherda; Mittal, Kanchan; Astha (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to compare the central corneal thickness (CCT) of primary open-angle glaucoma (POAG) patients with healthy subjects. Methods: A prospective, hospital-based, cross-sectional study conducted on total 100 consecutive subjects of age 40–60 years, 50 subjects of POAG, and 50 healthy controls presenting to the eye OPD in study period August 2021 to July 2022, at Department of Ophthalmology, Sardar Patel Medical College and Associated Group of Hospital, Bikaner, Rajasthan. Results: Mean age was 49.56±7.17 years in Group A and 52.36±7.86 years in Group B (p>0.05). 40% had 6/9 vision followed by 34% had 6/6 vision in Group A and 44% had 6/9 vision followed by 40% 6/12 vision in Group B (p<0.05). All cases in Group A had intraocular pressure (IOP) of 10–20 mmHg and 60% had IOP of 21.1–25.0 mmHg. (p<0.05). Mean CCT was 545.2±38.51 μm in Group A and 519.35±40.52 μm in Group B (p<0.05). Conclusion: Patients with thin corneas are more likely to develop POAG.